PENGGUNAAN MEDIA MATRAS BIDANG MIRING UNTUK MENINGKATKAN HASIL BELAJAR GULING DEPAN PADA SISWA KELAS 4 SD NEGERI PLOSOWANGI - FATKHUROHMAN FATKHUROHMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Student learning outcomes in front roll floor gymnastics are still low, one of the efforts that will be made to improve or improve the learning outcomes of front rolling floor gymnastics in grade 4 learning at SD Negeri Plosowangi using oblique mattress media. This Class Action Research is carried out in two cycles. Each cycle is carried out activities consisting of planning, implementing, observing and reflecting. The results of the research during the teaching and learning process showed an increase in students' ability to learn front roll floor gymnastics using inclined plane mattress media. In the first cycle, student learning completion reached 68.42% or a total of 13 students and those who were still below KKM were 6 students or as many as 31.57% still not enough of the desired percentage of learning completion. In the second cycle, the complete learning completion of students reached 89.47% or a total of 17 students who had successfully achieved a score above KKM and those who were still below KKM were 2 students or as many as 10.52%. Thus, this research can be stated that through the use of oblique field mattress media can improve the learning outcomes of front bolsters in grade 4 students of SD Negeri Plosowangi for the 2022/2023 academic year. ABSTRAKHasil belajar siswa pada senam lantai guling depan masih rendah, salah satu upaya yang akan dilakukan untuk memperbaiki ataupun meningkatkan hasil belajar senam lantai guling depan pada pembelajaran penjas kelas 4 di SD Negeri Plosowangi dengan menggunakan media matras miring. Penelitian Tindakan Kelas ini dilaksanakan dalam dua siklus. Setiap siklus dilaksanakan kegiatan yang terdiri dari perencanaan, pelaksanaan, pengamatan dan refleksi. Hasil penelitian selama proses belajar mengajar berlangsung, menunjukkan adanya peningkatan kemampuan siswa dalam pembelajaran senam lantai guling depan menggunakan media matras bidang miring. Pada siklus I ketuntasan belajar siswa mencapai 68,42 % atau sejumlah 13 siswa dan yang masih di bawah KKM adalah 6 siswa atau sebanyak 31,57 % masih belum cukup dari prosentase ketuntasan belajar yang diinginkan. Pada siklus II ketuntasan belajar siswa yang tuntas mencapai 89,47 % atau sejumlah 17 siswa yang telah berhasil mencapai nilai diatas KKM dan yang masih dibawah KKM adalah 2 siswa atau sebanyak 10,52 %. Dengan demikian penelitian ini dapat dinyatakan bahwa melalui penggunaan media matras bidang miring dapat meningkatkan hasil belajar guling depan pada siswa kelas 4 SD Negeri Plosowangi Tahun pelajaran 2022/2023.